Fracture Resistance Of Maxillary Premolar With Class II MOD Cavities Filled With Novel Composites Namely Nanohybrid Composite, Nanoceramic Composite, Short Fiber Enforced Composite And Nanohybrid With Fiber Splint Reinforced Composite - Damodhar, Ippar Priyanka; Varghese, Rana k; Arvind, Uge Anushri; Dubey, Astha; Jaiswal, Shreeya; Mohanty, Sandeep (Journal of Neonatal Surgery, 2025)
Aim: The aim of this study is to evaluate the fracture resistance of maxillary premolar with class II MOD cavities filled with novel composites namely nanohybrid composite, nanoceramic composite, short fiber enforced composite and nanohybrid with fiber splint reinforced composite. Materials and methods: This in-vitro study utilized 100 freshly extracted non-carious maxillary premolars, sourced from patients aged 20–45 years for orthodontic purposes at New Horizon Dental College and affiliated camps. The selected teeth met strict inclusion criteria, ensuring absence of cracks, caries, or anatomical anomalies. Teeth were stored in 10% formalin at room temperature until use, then mounted in acrylic blocks for testing.Teeth were randomly divided into five groups of 20 each. The positive control group consisted of intact, unrestored teeth, while the negative control group had MOD cavities left unrestored. The remaining groups had standardized MOD cavities prepared using diamond burs under air-water cooling. Cavity dimensions were maintained with precision using a digital caliper. The teeth were restored with one of the following: nanohybrid composite (Tetric N-Ceram), nanoceramic composite (Magma NT), short fiber reinforced composite (GC everX Posterior) with a nanohybrid surface layer, and nanohybrid composite reinforced with a fiber splint (Angelus Interlig). Results: Statistical analysis was first made by Kruskal Wallis Test, which showed significant difference of fracture resistance between the groups as a whole (H=88.44, p value<0.0001). Further it was analyzed by Mann Whitney U Test for 2- group comparison, the test showed highly significant statistical differences between all the study groups except between Group -II and Group –IV Conclusion: Within the limitations of this study, it can be concluded that the preparation of MOD cavities reduced the fracture resistance of maxillary premolars. Among the restorative materials tested under compressive loads, nanoceramic composites demonstrated the lowest fracture resistance, while nanohybrid and fibre-reinforced composite resins exhibited higher and comparable fracture resistance. Notably, the fibre-reinforced composite group showed superior reinforcing ability, as indicated by the favorable fracture patterns observed.